PEMBUATAN VIDEO INFOGRAFIS UNTUK PROMOSI KOMUNITAS FAKTABAHASA BOGOR - Leni, Leni; Ananto, Purnomo (XXX-XXX)
The era has been moving forward nowadays. No more boundaries in eachcountry caused by limitless of information, therefore must be a unifier. The one is language. In this writing, the writer wants to promote a creation to support society, especially young people, to get more knowledge about learning international languages beside national language. And it will be bundled in the Faktabahasa Bogor Community. All information exists in the creation of infographic video. With any graphic asset, all compiled together to make people interested to watch, so the meanings can be conveyed as well to the audience. Through this creation become one important thing to promote Faktabahasa Bogor Community in order to be more known by people. The result will published on social media to reach scope widely.